Method of discrete sources for elliptic problems arising in supercollider simulation - Bogomolov, Ya.L.; Semenov, E.S.; Yunakovsky, A.D. (Нелинейные граничные задачи, 2005)
An electrodynamical system of energy accumulation (accelerating section of a supercollider) is synthesized. Some model elliptic problems (boundary, inverse spectral, scattering) concerning synthesis of the optimal structure are considered. Numerical algorithms basing on the method of discrete sources and singular value decomposition technique are developed. Numerical examples are presented.